2003
DOI: 10.1037/0090-5550.48.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of discrimination in hiring job applicants with disabilities: The role of disability type, job complexity, and public contact.

Abstract: To evaluate the effects of disability type, job complexity, and public contact on hiring decisions. Design and Participants: An Americans With Disabilities Act (ADA; 1990) fact sheet and matched resumes with vocational and medical histories including chronic mental illness, developmental disability, closed head injury, and back injury were provided to 295 undergraduate business-related majors, who rated the applicants' suitability for 2 job positions and work shifts. Results: Findings indicated disparities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 9 publications
2
92
4
1
Order By: Relevance
“…Most of the literature on the topic has revealed that people with disabilities are often viewed negatively (Barnes, 1992;Jayasooria et al, 1997;Gouvier et al, 2003;Haq, 2003;Brown et al, 2009). There is also a bias against meeting with them due to the prejudices and misconceptions prevalent among the public regarding their ability to perform and compete in the job market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the literature on the topic has revealed that people with disabilities are often viewed negatively (Barnes, 1992;Jayasooria et al, 1997;Gouvier et al, 2003;Haq, 2003;Brown et al, 2009). There is also a bias against meeting with them due to the prejudices and misconceptions prevalent among the public regarding their ability to perform and compete in the job market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arvey (1979) suggested that forced ranks are more sensitive than ratings to subtle biases. Research findings support Arvey's position (Dipboye et al, 1975;Gouvier et al, 2003). The present study attempted to avoid these and other methodological pitfalls by using both ratings and ranking of written resumés specifically with HR recruitment professionals.…”
Section: Methodological Considerations In Resumé Evaluation Researchmentioning
confidence: 67%
“…Furthermore, the majority of studies of gender and ethnicity effects on resumé evaluations have used participants' ratings as the dependent measure, although some studies have incorporated forced-choice ranking of resumés (Ding & Stillman, 2005;Gouvier et al, 2003;Marlowe et al, 1996). Arvey (1979) suggested that forced ranks are more sensitive than ratings to subtle biases.…”
Section: Methodological Considerations In Resumé Evaluation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reliance on traditional statistical approaches such as analysis of variance has limited the capacity to examine within-person effects of factors like perceived cost and necessity on the decision to grant (e.g., Florey & Harrison, 2000;Gouvier et al, 2003). Finally, some existing studies have relied on student samples rather than using managers and HR professionals who are required to make accommodation requests as part of their job (e.g., Gouvier et al, 2003;Hazer & Bedell, 2000).…”
Section: Introductionmentioning
confidence: 99%